PEMANFAATAN LIMBAH PERCA PADA PENGEMBANGAN BUSANA READY TO WEAR MENGGUNAKAN TEKNIK PATCHWORK DENGAN SUMBER IDE PANDEMI COVID-19 - Putri Mayang Anggraini (Jurnal BOSAPARIS: Pendidikan Kesejahteraan Keluarga, 2023)
This research aims to (1) describe the process of utilizing textile waste in the development of ready-to-wear fashion using patchwork techniques with the idea source of the COVID-19 pandemic, and (2) describe the quality of the results obtained from the utilization of textile waste in the development of ready-to-wear fashion using patchwork techniques with the idea source of the COVID-19 pandemic. The method used in this research is Research and Development (R&D) with the PPE development model, consisting of three stages: planning, production, and evaluation. Data collection method utilized in this research is through questionnaires or surveys, then analyzed using quantitative descriptive techniques. This research produced ready to wear fashion products in the form of jackets and utilized patchwork as decoration with the source idea of the covid-19 pandemic. In the planning stage, the researcher collected references to turn sketches into actual design prototypes. Subsequently, the production stage involved several steps, including preparation and implementation. The final stage was evaluation, where the shortcomings in the development of ready-to-wear fashion were assessed. The results obtained from the quality assessment showed excellent qualifications based on the achievement level convention table with a percentage of 96.53%, this indicates that the produced products adhere to design principles.